Ionic liquids interacting with small molecules and a gold (110) surface - Buckley, Matthew (2016)
This thesis presents investigations into the interactions of ionic liquids (ILs). An investigation on the interaction of the ionic liquid 1-octyl-3-methylimidazolium tetrafluoroborate ([C8C1Im][BF4]) with three small molecules will focus on how the desorption kinetics are perturbed by interaction with the IL. A monolayer of 1-ethyl-3-methylimidazolium bis[(trifluoromethyl)sulfonyl]imide ([C2C1Im][NTf2]) interacting with a Au(110) crystal facet is investigated using normal incidence x-ray standing wave (NIXSW) to resolve positional information. Acetone, sulfur dioxide and water interacting with [C8C1Im][BF4] are investigated. The desorption of pure species has been characterised. Acetone multilayers desorb with an activation energy of Ea = 38(2) kJ mol^-1 and a pre-exponential of A = 4.3x10^14(1) s^-1. Sulfur dioxide desorbs with an activation energy of Ea = 32(2) kJ mol^-1 and a pre-exponential of A = 6x10^14(1) s^-1. Water is observed to have an amorphous to crystalline phase change over the desorption region. Amorphous water is calculated to have a desorption activation energy of Ea = 49(5) kJ mol^-1 compared to Ea = 43(2) kJ mol^-1 for crystalline water. The pre-exponential is calculated to be A = 10^17(2) s^-1 and A = 10^15(1) s^-1 for the amorphous and crystalline water respectively. [C8C1Im][BF4] is found to stabilise both acetone and sulfur dioxide to a fixed capacity. A mole fraction of 1.2 of acetone to [C8C1Im][BF4] was stabilised over a range of Ea = 45 – 61 kJ mol^-1. A mole fraction of 6 of sulfur dioxide to [C8C1Im][BF4] was stabilised over a range of Ea = 40 – 52 kJ mol^-1. No fixed capacity was found for water despite being in great excess of the [C8C1Im][BF4]. The full coverage of water was influenced by the presence of [C8C1Im][BF4] with an activation energy of Ea = 42 kJ mol^-1 at full water coverage which increased to Ea = 49 kJ mol^-1 as the water coverage tended to zero. Several possible positions of [C2C1Im][NTf2] on Au(110) are presented. Near edge absorption fine structure (NEXAFS) spectroscopy informed that the imidazolium ring is flat on the surface. The position of the cation and the anion on the surface is found through simulation of each ion separately. The NIXSW is used to propose two real space position which the cation could occupy. The position of the anion is reduced to five possible configurations on the surface through the use of NIXSW.